Wyeomyia (Miamyia) argentina, a new species of mosquito (Diptera: Culicidae) from Argentina - Stein, Marina; Bangher, Débora Natalia; Neves, Maycon Sebastião Alberto Santos; Alvarez, Carla Noel (Zootaxa, 2026)
Wyeomyia (Miamyia) argentina, a new mosquito species from Corrientes Province, northeastern Argentina, is described based on morphological characters of the adult female and male, male genitalia, pupa and fourth-instar larva. Morphological characteristics of Wy. argentina are compared with other species of subgenus Miamyia. Phylogenetic relationships are discussed.